Patient’s attitude and knowledge towards the usage of barrier technique by orthodontists. - Shyagali, Tarulatha R; Bhayya, Deepak P (International Journal of Infection Control, 2012)
The article aimed to assess the patient’s attitude and knowledge towards the use of barrier technique by the orthodontists. One hundred orthodontic patients of age 15-20 years, who visited the department of orthodontics, Darshan dental college, Udaipur, were randomly selected and asked to fill the questionnaire of ten questions related to the usage of barrier technique by the orthodontists. The collected data was subjected to descriptive statistical analysis and chi-square tested was performed to evaluate the difference between the genders. Ninety six percent of patients felt orthodontist should wear gloves and 98% wanted their orthodontist to wear mouth mask, 74% of patients thought that both orthodontist and the patients will be protected from the spread of the infection and 58% of them also wanted orthodontist to wear protective glasses during the treatment procedure. Eighty eight percent of them refused the treatment by orthodontists who were not wearing the gloves and 75% wanted the gloves to be changed for each patient. Significant difference was seen between females and males for the attitude towards the barrier technique used by the orthodontist. High level of awareness is seen in the present group of orthodontic patients and this warns the orthodontic to review their infection control strategies.